Peningkatan Ekonomi Ampas Tahu Menggunakan Mesin Pengering Teknologi Rotary Untuk Membuat Bahan Tepung dan Pakan - Tri Hartutuk Ningsih; Bellina Yunitasari (Universitas Muhammadiyah Sidoarjo, 2019)
The purpose of this program is to provide solutions to the problems that exist in tofu production SMEs, especially the problem of processing side effects of waste production which so far has not been maximally utilized, the production waste in the form of tofu waste can be utilized as a high economic value product. The method used is the process of drying the tofu dregs using rotary technology and the heat exchanger technology used to dry the tofu dregs and this tool is equipped with an automatic temperature regulator which is used to control the temperature in the drying tube. By using this machine, the wet tofu dregs can be dried quickly and the resulting color remains white (as in wet conditions). Based on the results of the drying test, the economic value of tofu waste can increase the economic value of tofu waste which initially only Rp. 10,000 to Rp. 63,000 per bag.